Reflection of the status of women in medieval fergana valley society in historical sources - Yuldashev, Saidanvarbek Bakhromjon o‘g‘li (The Lingua Spectrum, 2026)
Based on historical sources and scholarly literature, this article examines the role and status of women in the socio-political life of the Fergana Valley during the Early Middle Ages. Particular attention is given to the queens of the Fergana state in the 640s and to the influence of women on political processes during the period of the Arab conquest. The study highlights the significance of women in governance and their contribution to the social and political development of the region.